Hubungan Masa Kerja dan Postur Kerja dengan Keluhan Musculoskeletal Disorders (MSDs) pada Pekerja Mekanik di Bengkek Mobil Kisaran Fantasi - Pratiwi, Dwika Ardelya; Nanda, Meutia; Wasiyem, Wasiyem (Jurnal Kesehatan Komunitas, 2025)
Musculoskeletal Disorders (MSDs) are complaints often experienced by workers who work in non-ergonomic conditions. The Kisaran Fantasi workshop is one of the car repair shops where workers bend, stoop, bend their wrists, and squat repeatedly when repairing cars for a long time. This causes workers to often feel pain in the back, calves, and numbness in the wrists. This study aims to determine the relationship between tenure and work posture with complaints of Musculoskeletal Disorders (MSDs) in mechanical workers at the Kisaran Fantasi car repair shop. The method in this study is descriptive quantitative with a cross-sectional design. The sample in this study used a total sampling technique of 55 workers. This research was conducted in January 2025. The analysis used in this study used univariate and bivariate tests and the chi-square test. The results showed that there was a relationship between length of service (P-value = 0.048) and work posture (P-value = 0.005) with complaints of Musculoskeletal Disorders (MSDs) in the Fantasy Range workshop. In conclusion, there is a significant relationship between length of service and work posture and Musculoskeletal Disorders (MSDs) complaints in the Fantasy Range workshop, all of which have a p-value > 0.05. Advice for workers to pay attention to posture while working, and advice for auto repair shop owners to provide additional assistance, such as wellness programs or referrals to medical specialists, for workers who are sick.